Effect and Management of Excess Weight in the Context of Fertility-Sparing Treatments in Patients With Atypical Endometrial Hyperplasia and Endometrial Cancer: Eight-Year Experience of 227 Cases - Shan, Ying; Qin, Meng; Yin, Jie; Cai, Yan; Li, Yan; Gu, Yu; Wang, Wei; Wang, Yong-xue; Chen, Jia-yu; Jin, Ying; Pan, Ling-ya (Frontiers in Oncology, 2021)
Objective: To investigate the oncologic and reproductive outcomes of fertility-sparing treatments (FSTs) in atypical endometrial hyperplasia (AEH) and endometrial cancer (EC) patients with excess weight (EW). Methods: This retrospective study comprised patients with AEH or EC who achieved a complete response (CR) after FST from 2010 to 2018. The clinical characteristics, oncologic and reproductive outcomes were compared between excess weight (EW) group (BMI≥25 kg/m2) and normal weight (NW) group (BMI<25 kg/m2). The risk factors associated with recurrence and infertility for patients of EW were analyzed. Results: Overall, 227 patients were collected, including 139 (61.2%) in EW group and 88 (38.8%) in NW group. In patients with EW, the pregnancy rate, the live birth rate and the relapse rate were respectively 29.8%, 23.4%, and 30.9%. While in patients with NW, these rates were respectively 61.1%, 47.2%, and 31.8%. No significant differences were observed in the time to remission (P=0.865) and DFS (P=0.750). The patients in NW group had better pregnancy rate than in EW group (P=0.034). The patients with EW using letrozole for ovulation induction tend to have an increased rate of pregnancy (P=0.042). However, there were no significant risk factors associated with unsuccessful pregnancy after the multivariate analysis. In terms of disease-free survival (DFS), the combination of gonadotropin-releasing hormone agonist (GnRH-a) and LNG-IUD was better for patients with EW than only GnRH-a or oral progestin therapy (P=0.044, adjusted HR=0.432, 95% CI: 0.152-1.229), especially for EC patients with EW (P=0.032). Conclusion: FSTs for overweight and obese patients should be more individualized. GnRH-a and/or LNG-IUD may be optimal options for FSTs in patients with EW. Further prospective studies are needed.